Carbon fiber in-situ conversion skin-core structure superhigh temperature carbide ceramic fiber and preparation method thereof

By performing molten salt distortion reaction in high-temperature liquid molten salt, ultra-high temperature carbide ceramic fibers with uniform tissue structure and strong adjustability were prepared, which solved the difficulty of preparing ultra-high temperature ceramic fibers in the prior art. The problem of poor process stability of Yamato achieves fiber preparation with high strength and high temperature performance.

CN119263838APending Publication Date: 2025-01-07NAT UNIV OF DEFENSE TECH
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411513200.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing ultra-high temperature ceramic fibers are difficult to prepare and process stability are difficult to guarantee, resulting in limited application in the aerospace field.

Method used

The preparation method of ultra-high temperature carbide ceramic fibers in situ converted into the scald core structure of carbon fibers is adopted. By performing the molten salt distortion reaction in the high-temperature liquid molten salt, a fine and uniform ultra-high temperature ceramic layer is generated, and the scald core ratio is controlled to form a continuous and Fiber with antioxidant properties.

Benefits of technology

It realizes ultra-high temperature ceramic fibers with uniform tissue structure and strong adjustability. The process is stable and controllable, with short cycles and low cost. The fiber tensile strength is between 1.49GPa and 2.90GPa, and it has antioxidant, high temperature resistance and good continuity. , high strength and comprehensive performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263838A_ABST
    Figure CN119263838A_ABST
Patent Text Reader

Abstract

The invention discloses a carbon fiber in-situ conversion skin-core structure superhigh temperature carbide ceramic fiber and a preparation method thereof. The fiber is composed of a surface layer and a carbon fiber core layer, and the surface layer is an ultrahigh-temperature ceramic phase of tantalum carbide, hafnium carbide, zirconium carbide or titanium carbide and is formed by performing a molten salt disproportionation reaction in high-temperature liquid molten salt. The preparation method comprises the following steps: placing the carbon fibers at the bottom of a graphite crucible, adding NaCl and KCl mixed salt as a molten salt medium, adding ultrahigh-temperature metal powder and corresponding transition metal fluoride to promote the reaction to permeate in the whole carbon fibers, and finally realizing the controlled growth of the ultrahigh-temperature ceramic fibers with different skin-core proportions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of ultra-high temperature ceramic fibers, and in particular relates to an ultra-high temperature carbide ceramic fiber with a skin-core structure obtained by in-situ conversion of carbon fibers and a preparation method thereof. Background Art

[0002] Continuous fiber reinforced ultra-high temperature ceramic matrix composites have the characteristics of anti-oxidation, high temperature resistance, and excellent high temperature mechanical properties. They are widely used in various rocket engines, high-speed aircraft and other important hot end components. As a reinforcement for ultra-high temperature ceramic matrix composites, it has the characteristics of ultra-high temperature resistance, small diameter, high strength, high modulus and high ablation resistance.

[0003] Ultra-high temperature ceramic fibers have attracted much attention for their excellent high-temperature performance, which is mainly manifested in the fact that they do not decompose or melt under extremely high temperature conditions. However, this feature also leads to more stringent requirements for the conditions in the preparation process. Domestic and foreign scholars have conducted in-depth research and exploration on the preparation methods of ultra-high temperature ceramic fibers, including the precursor conversion method and the sol-gel method. Although certain research progress has been made, there is no truly commercialized ultra-high temperature ceramic fiber in the world. Only the United States has demonstrated continuous TaC and HfC ultra-high temperature ceramic fibers. However, the fibers reported above have rarely been used in the aerospace field. It can be inferred that factors such as the difficulty of preparation and the difficulty in ensuring process stability have restricted their development.

[0004] The core of the skin-core ultra-high temperature ceramic fiber is a carbon phase, and the outer layer is a ceramic phase. The carbon phase plays a role of continuity and high strength, and the ceramic phase plays an antioxidant role. The use of appropriate preparation methods and process parameters can control the state of the skin ceramic phase, promote the continuous conversion reaction, and convert the carbon fiber into a skin-core ultra-high temperature ceramic fiber.

[0005] Therefore, the research focus of researchers at home and abroad has gradually shifted from exploring stable ultra-high temperature ceramic precursors to using appropriate preparation methods to obtain ultra-high temperature carbide ceramic fibers with skin-core structure and adjustable skin-core ratio. Summary of the invention

[0006] In view of the difficulty in preparing ultra-high temperature ceramic fibers in the prior art, the present invention provides an ultra-high temperature carbide ceramic fiber with a skin-core structure converted by in-situ conversion of carbon fibers and a preparation method thereof, so as to solve the technical problems that the preparation of ultra-high temperature ceramic fibers is difficult and the process stability is difficult to ensure. The ultra-high temperature carbide ceramic fiber with a skin-core structure converted by in-situ conversion of carbon fibers prepared by the present invention has the characteristics of uniform organizational structure and high adjustability; the preparation method of an ultra-high temperature carbide ceramic fiber with a skin-core structure converted by in-situ conversion of carbon fibers has the advantages of stable and controllable process, short cycle, low cost, and strong designability.

[0007] The technical solution of the present invention is as follows:

[0008] The carbon fiber is placed at the bottom of a graphite crucible, a mixed salt of NaCl and KCl is added as a molten salt medium, and ultra-high temperature metal powder and corresponding transition metal fluoride are added, so that the carbon fiber and the metal source undergo a molten salt disproportionation reaction in the high-temperature liquid molten salt to generate an ultra-high temperature ceramic layer. The ceramic layer has fine and uniform grains, which enables the molten salt disproportionation reaction to continuously penetrate into the interior of the carbon fiber, and finally ultra-high temperature ceramic fibers with different skin-core ratios are obtained by controlling the reaction parameters;

[0009] The obtained carbon fiber in-situ converted skin-core structure ultra-high temperature carbide ceramic fiber has a skin-core structure, including a skin layer of the ultra-high temperature ceramic phase obtained by the reaction, and a carbon fiber core layer remaining from the reaction;

[0010] The ultra-high temperature ceramic phase is one of tantalum carbide (TaC), hafnium carbide (HfC), zirconium carbide (ZrC) and titanium carbide (TiC).

[0011] The purpose of the present invention is achieved through the following technical solutions:

[0012] A carbon fiber in-situ conversion skin-core structure ultra-high temperature carbide ceramic fiber, the skin-core structure consists of a skin layer and a core layer, the skin layer is an ultra-high temperature carbide ceramic phase, and the core layer is a carbon fiber; the carbon fiber is selected from one of polyacrylonitrile-based fiber, asphalt-based fiber, one-dimensional fiber monofilament, and two-dimensional woven structure;

[0013] The ratio of the thickness of the epidermis layer to the fiber diameter is in the range of 5-90%;

[0014] The grain size of the epidermis is 40-300 nm, and the ultra-high temperature ceramic phase is one of tantalum carbide (TaC), hafnium carbide (HfC), zirconium carbide (ZrC), and titanium carbide (TiC);

[0015] The obtained carbon fiber in-situ converted skin-core structure ultra-high temperature carbide ceramic fiber has adjustable high temperature and mechanical properties. The prepared carbon fiber in-situ converted skin-core structure ultra-high temperature carbide ceramic fiber has a tensile strength of 1.49GPa-2.90GPa.

[0016] In the present invention:

[0017] Preferably, the ratio of the thickness of the epidermis to the fiber diameter is in the range of 10-70%. The skin-core structured ultra-high temperature carbide ceramic fiber in this range can not only enable the carbon fiber to exhibit the characteristics of good continuity and easy weaving, but also ensure that there are sufficient ultra-high temperature ceramic phases to exhibit antioxidant and high temperature resistant effects, so that the skin-core structured ultra-high temperature carbide ceramic fiber has comprehensive properties such as antioxidant, high temperature resistant, good continuity, and high strength and toughness.

[0018] The present invention also relates to a method for preparing the above-mentioned carbon fiber in-situ conversion skin-core structure ultra-high temperature carbide ceramic fiber, comprising the following steps:

[0019] 1) Placing carbon fiber at the bottom of a graphite crucible and adding mixed salt as a molten salt medium;

[0020] The mixed salt is NaCl and KCl, wherein the molar ratio of NaCl to KCl is 1:(0.8-1.2);

[0021] 2) adding ultra-high temperature metal powder and transition metal fluorate, so that the carbon fiber and the metal source undergo molten salt disproportionation reaction in a high-temperature liquid molten salt to generate an ultra-high temperature ceramic layer, wherein the transition metal is one of Ti, Zr, Hf and Ta; the transition metal fluorate is one of K2TiF6, K2ZrF6, K2HfF6 and K2TaF7; the molar ratio of the carbon fiber, transition metal powder, transition metal fluorate and molten salt medium is 1:(0.09-0.3):(0.03-0.1):(5-10); the temperature of the molten salt disproportionation reaction is 800-1200°C, the temperature is increased at 5-15°C / min, the insulation time is 1-10h, and the atmosphere is protected by argon; finally, an ultra-high temperature carbide ceramic fiber with a skin-core structure converted from the carbon fiber in situ is obtained, and the prepared ultra-high temperature carbide ceramic fiber with a skin-core structure converted from the carbon fiber in situ has a tensile strength of 1.49GPa-2.90GPa.

[0022] Compared with the prior art, the present invention has the following advantages:

[0023] 1. The present invention discloses an ultra-high temperature carbide ceramic fiber with a skin-core structure obtained by in-situ conversion of carbon fiber. The fiber has a skin-core structure and includes a skin layer of an ultra-high temperature ceramic phase obtained by reaction and a carbon fiber core layer remaining from the reaction; the ultra-high temperature ceramic phase is mainly one of tantalum carbide (TaC), hafnium carbide (HfC), zirconium carbide (ZrC), and titanium carbide (TiC). Compared with ultra-high temperature ceramic fibers prepared by traditional precursor conversion methods and sol-gel methods, the ultra-high temperature ceramic fiber with a skin-core structure of the present invention has the characteristics of good consistency of results and adjustable skin-core ratio.

[0024] 2. The method for preparing a carbon fiber in-situ conversion skin-core structure ultra-high temperature carbide ceramic fiber described in the present invention, the carbon fiber can be a high-strength fiber, a high-modulus fiber in a polyacrylonitrile-based fiber, or an asphalt-based fiber; the ultra-high temperature ceramic phase is mainly one of tantalum carbide (TaC), hafnium carbide (HfC), zirconium carbide (ZrC), and titanium carbide (TiC). The method requires simple equipment, stable process, and can be carried out at a relatively low reaction temperature; at the same time, the generated ultra-high temperature ceramic phase has the characteristics of fine grains, and the reactants can continue to penetrate into the carbon core, promoting the continuous occurrence of the reaction. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0026] Figure 1 SEM photos of skin-core structured ultra-high temperature carbide ceramic fibers (HfC fibers) with different skin-core ratios prepared in embodiments of the present invention;

[0027] Figure 2 This is a SEM image of the skin-core structure ultra-high temperature carbide ceramic fiber prepared in Example 1 of the present invention;

[0028] Figure 3 This is a SEM image of the skin-core structure ultra-high temperature carbide ceramic fiber prepared in Example 2 of the present invention;

[0029] Figure 4 This is a SEM image of the skin-core structure ultra-high temperature carbide ceramic fiber prepared in Example 3 of the present invention;

[0030] Figure 5 Schematic diagram of the in-situ conversion of carbon fiber into skin-core structure ultra-high temperature carbide ceramic fiber obtained in Example 1 of the present invention (wherein: 1, skin-core structure; 11, skin layer; 12, core layer). DETAILED DESCRIPTION

[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] In addition, the technical solutions between the various embodiments of the present invention can be combined with each other, but it must be based on the fact that ordinary technicians in the field can implement it. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0033] Unless otherwise specified, all drugs / reagents used were commercially available.

[0034] Embodiment 1:

[0035] A method for preparing an ultra-high temperature carbide ceramic fiber with a skin-core structure by in-situ conversion of carbon fiber, which comprises the following steps:

[0036] Weigh 12.0g of polyacrylonitrile-based carbon fiber, 32.6g of Ta powder, 23.6g of K2TaF7 powder, 146.25g of NaCl powder, and 186.3g of KCl powder, mix the four evenly and pour them into a crucible, then place the crucible in a cracking furnace for molten salt reaction. The reaction temperature is 1100℃, the reaction time is 3h, the reaction atmosphere is argon, and after cooling, the product is washed with water to obtain a skin-core structure TaC@C ultra-high temperature ceramic fiber.

[0037] Figure 2 The carbon fiber prepared in this embodiment is an ultra-high temperature carbide ceramic fiber with a skin-core structure through in-situ conversion.

[0038] Depend on Figure 2 It can be seen that the fiber prepared in this embodiment has an obvious skin-core structure, in which the outer layer of ultra-high temperature ceramic fine-grained TaC layer is uniformly coated on the surface of the carbon fiber, and the core is unreacted carbon fiber.

[0039] Figure 5 Schematic diagram of the in-situ conversion of carbon fiber into skin-core structure ultra-high temperature carbide ceramic fiber obtained in Example 1, wherein the in-situ conversion of carbon fiber into skin-core structure ultra-high temperature carbide ceramic fiber comprises a skin-core structure (1), characterized in that the skin-core structure (1) consists of a skin layer (11) and a core layer (12), the skin layer (11) is an ultra-high temperature carbide ceramic phase, and the core layer (12) is carbon fiber.

[0040] The tensile strength of the fiber is tested according to the test standard GB / T31290-2014 "Determination of tensile properties of carbon fiber monofilaments". The tensile strength of the carbon fiber in-situ conversion skin-core structure ultra-high temperature carbide ceramic fiber prepared in Example 1 is 2.9 GPa (there is currently no separate way to characterize the high temperature performance of the fiber, and there is no corresponding test standard to standardize it. All of them reflect their contribution to high temperature resistance in the form of composite materials. Therefore, the present invention only characterizes the mechanical properties test of the fiber).

[0041] Embodiment 2:

[0042] A method for preparing an ultra-high temperature carbide ceramic fiber with a skin-core structure by in-situ conversion of carbon fiber is a method for preparing an ultra-high temperature carbide ceramic fiber with a skin-core structure by in-situ conversion of carbon fiber, comprising the following steps:

[0043] Weigh 12.0g of polyacrylonitrile-based carbon fiber, 32.1g of Hf powder, 22.2g of K2HfF6 powder, 146.25g of NaCl powder, and 186.3g of KCl powder, mix the four evenly and pour them into a crucible, then place the crucible in a cracking furnace for molten salt reaction. The reaction temperature is 1200℃, the reaction time is 5h, the reaction atmosphere is argon, and after cooling, the product is washed with water to obtain a skin-core structure HfC@C ultra-high temperature ceramic fiber.

[0044] Figure 3 The carbon fiber prepared in this embodiment is an ultra-high temperature carbide ceramic fiber with a skin-core structure through in-situ conversion.

[0045] Depend on Figure 3 It can be seen that the fiber prepared in this embodiment has an obvious skin-core structure, wherein the outer ultra-high temperature ceramic HfC layer is uniformly coated on the surface of the carbon fiber, and the core is unreacted carbon fiber.

[0046] The tensile strength of the fiber was tested according to the test standard GB / T31290-2014 "Determination of tensile properties of carbon fiber monofilaments". The tensile strength of the carbon fiber in-situ converted skin-core structure ultra-high temperature carbide ceramic fiber prepared in Example 2 was 1.49 GPa.

[0047] Embodiment 3:

[0048] A method for preparing an ultra-high temperature carbide ceramic fiber with a skin-core structure by in-situ conversion of carbon fiber, which comprises the following steps:

[0049] Weigh 12.00g of asphalt-based carbon fiber, 16.3g of Ta powder, 11.8g of K2TaF7 powder, 146.25g of NaCl powder, and 186.3g of KCl powder, mix the four evenly and pour them into a crucible, then place the crucible in a cracking furnace for molten salt reaction. The reaction temperature is 1000℃, the reaction time is 1h, the reaction atmosphere is argon, and after cooling, the product is washed with water to obtain a skin-core structured TaC@C ultra-high temperature ceramic fiber.

[0050] Figure 4 This is the sheath-core structure fiber prepared in this example.

[0051] As can be seen from the figure, the fiber prepared in this embodiment has an obvious skin-core structure, in which the outer layer of ultra-high temperature ceramic fine-grained TaC layer is evenly coated on the surface of the carbon fiber, and the core is unreacted asphalt-based carbon fiber.

[0052] The tensile strength of the fiber was tested according to the test standard GB / T31290-2014 "Determination of tensile properties of carbon fiber monofilaments". The tensile strength of the carbon fiber in-situ converted skin-core structure ultra-high temperature carbide ceramic fiber prepared in Example 3 was 2.23 GPa.

[0053] It is to be understood that the present invention is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present invention. In addition, under the teachings of the present invention, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the spirit and scope of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of this application are within the scope of protection of the present invention.

Claims

1. A carbon fiber in-situ conversion skin-core structure ultra-high temperature carbide ceramic fiber, characterized in that: The skin-core structure is composed of a skin layer and a core layer, the skin layer is an ultra-high temperature carbide ceramic phase, and the core layer is carbon fiber; the carbon fiber is selected from one of polyacrylonitrile-based fiber, asphalt-based fiber, one-dimensional fiber monofilament, and two-dimensional woven structure; The ratio of the thickness of the epidermis layer to the fiber diameter is in the range of 5-90%; The grain size of the epidermis is 40-300 nm, and the ultra-high temperature ceramic phase is one of tantalum carbide, hafnium carbide, zirconium carbide and titanium carbide; The obtained carbon fiber in-situ converted skin-core structure ultra-high temperature carbide ceramic fiber has adjustable high temperature and mechanical properties. The prepared carbon fiber in-situ converted skin-core structure ultra-high temperature carbide ceramic fiber has a tensile strength of 1.49GPa-2.90GPa.

2. The carbon fiber in-situ conversion skin-core structure ultra-high temperature carbide ceramic fiber according to claim 1, characterized in that: The ratio of the thickness of the epidermis layer to the fiber diameter is in the range of 10-70%.

3. The method for preparing a carbon fiber in-situ converted skin-core structure ultra-high temperature carbide ceramic fiber according to claim 1 or 2, characterized in that: The following steps are involved: 1) Placing carbon fiber at the bottom of a graphite crucible and adding mixed salt as a molten salt medium; The mixed salt is NaCl and KCl, wherein the molar ratio of NaCl to KCl is 1:(0.8-1.2); 2) adding ultra-high temperature metal powder and transition metal fluorate, so that the carbon fiber and the metal source undergo molten salt disproportionation reaction in a high-temperature liquid molten salt to generate an ultra-high temperature ceramic layer, wherein the transition metal is one of Ti, Zr, Hf and Ta; the transition metal fluorate is one of K2TiF6, K2ZrF6, K2HfF6 and K2TaF7; the molar ratio of the carbon fiber, transition metal powder, transition metal fluorate and molten salt medium is 1:(0.09-0.3):(0.03-0.1):(5-10); the temperature of the molten salt disproportionation reaction is 800-1200°C, the temperature is increased at 5-15°C / min, the insulation time is 1-10h, and the atmosphere is protected by argon; finally, an ultra-high temperature carbide ceramic fiber with a skin-core structure converted from the carbon fiber in situ is obtained, and the prepared ultra-high temperature carbide ceramic fiber with a skin-core structure converted from the carbon fiber in situ has a tensile strength of 1.49GPa-2.90GPa.

Citation Information

Patent Citations

  • Preparation method for in-situ synthesis of Ti3SiC2 interface phase on surface of SiC fiber by using SiC nanocrystals

    CN113087533A

  • Ultrahigh-temperature ceramic composite material with fiber monolithic structure and preparation method thereof

    CN113896553A

  • C / C-UHTCs composite material containing nano complex-phase ultrahigh-temperature ceramic inner coating and preparation method of C / C-UHTCs composite material

    CN116239400A